The Effect of Internship Experience, Career Guidance, and Self-Confidence on the Work Readiness of 2021 Students in the Management Study Program, Faculty of Economics, Sarjanawiyata Tamansiswa University, Yogyakarta - Ela Nuraini (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This research tends to examine the extent to which internship experience, career guidance, and self-efficacy influenced students’ work readiness. The research involved 72 respondents who were college students of class of 2021 in the Management Study Program, Faculty of Economics, at Sarjanawiyata Tamansiswa University, Yogyakarta. Data were collected by distributing online questionnaires using Google Forms. The sampling method applied was non-probability sampling with an incidental approach. The collected data were examined using SPSS version 26. The outcomes indicate that internship experience, career guidance, and self-efficacy have a positive and significant effect on students’ work readiness. Therefore, these three factors are essential to be developed and strengthened in order to arrange students for the challenges of the professional field. This study implies that improving students' work readiness is not only the responsibility of individual students, but also of the university as a whole. Universities must create an educational environment that supports the growth of competence, confidence, and readiness to face the work field.